The Implication of SEMA No 2/2023 on the Protection of Administrative Rights in Interfaith Marriage - Thesalonika, Anggun Azzahra; Hasanudin, Fuat (Qanun: Jurnal Hukum Keluarga Islam, 2025)
Interfaith marriage is an inevitable phenomenon in pluralistic societies like Indonesia. Although the Marriage Law does not explicitly prohibit it, the Law on Population Administration provides legal space for interfaith couples to register their marriage through a court ruling. In response to this, the Supreme Court issued SEMA No 2/2023 as a guideline for judges in adjudicating cases related to the registration of marriages between individuals of different religions and beliefs. This study aims to understand the background and objectives of the issuance of this Circular Letter, as well as its implementation regarding the protection of the administrative rights of interfaith couples at the Surakarta District Court. The research employs a field research method with an empirical juridical approach, with data obtained through interviews with three judges. The findings reveal that SEMA No 2/2023  is used as a legal basis by judges in deciding cases related to the registration of interfaith marriages, in order to ensure consistency and legal certainty. The views of the judges at the Surakarta District Court indicate that SEMA No 2/2023 is positioned as a legal guide in assessing applications for the registration of interfaith marriages. Despite receiving criticism, the Circular has been met with a positive response from the judges. In conclusion, SEMA No 2/2023 affirms that the validity of a marriage is recognized solely based on religious law and highlights the importance of adhering to legal provisions to safeguard the administrative rights of interfaith couples.